Comparison of high-flow nasal cannula oxygenation and non-invasive ventilation for postoperative pediatric cardiac surgery: a meta-analysis - Zhou, Si-Jia; Chen, Xiu-Hua; Liu, Ying-Ying; Chen, Qiang; Zheng, Yi-Rong; Zhang, Qi-Liang (BMC pulmonary medicine, 2024)
Objective To evaluate the efficacy of high-flow nasal cannula oxygenation (HFNC) versus non-invasive ventilation (NIV) in pediatric patients post-congenital heart surgery (CHS) through a meta-analysis. Methods A comprehensive literature search was conducted across the Chinese biomedical literature database, Vip database, CNKI, Wanfang, PubMed, Embase, Cochrane Library, and Web of Science until December 20, 2022. We selected RCTs or cohort studies that met inclusion criteria for a meta-analysis using RevMan 5.4 software. Results Our search yielded five publications, comprised of one randomized controlled trial and four cohort studies. Meta-analysis revealed a significant reduction in reintubation rates in children post-CHS treated with HFNC as compared to NIV [RR = 0.36, 95%CI(0.25 ~ 0.53), P < 0.00001]. There was also a notable reduction in the duration of ICU stay [MD = -4.75, 95%CI (-9.38 ~ -0.12), P = 0.04]. No statistically significant differences were observed between HFNC and NIV in terms of duration of mechanical ventilation, 24 h PaO 2 , and PaCO 2 post-treatment (P > 0.05). Furthermore, both groups showed no significant difference in the duration of extracorporeal circulation [MD = -8.27, 95%CI(-17.16 ~ 0.62), P = 0.07]. Conclusions For pediatric patients post-CHS, HFNC appears to be more effective than NIV in reducing reintubation rates and shortening the CICU stay.